Stratégies de subsistance et Perception des aliments des populations autochtones de Yakoutie arctique (Districts de Basse et de Moyenne Kolyma) - Christian Malet; Boris Chichlo; Joëlle Robert-Lamblin; Claude-Marcel Hladik; Patrick Pasquet (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
A study of food preferences of the indigenous peoples of Arctic Yakutia was conducted on a population sample consisting of 102 Evens, 52 Yakuts and 22 Chukchis. Responses recorded on analogue scales corresponding to 69 food items have been supplemented by blind tests concerning the perception of solutions of sucrose, sodium chloride, and PROP, to determine hedonic responses to salt and to sucrose (sweet likers vs. sweet dislikers) and the PROP status (tasters vs. non-tasters). Data were computed in relation to age, sex, ethnic groups and ecological factors. Subsistence patterns and food preferences appear to be related, and significant ethnic differences in mean preferences mirror the environmental and historical backgrounds of the various populations. Sensory factors, and notably the PROP status, do not appear as significantly determining food preferences.